Evaluasi Pengaruh Umur yang Berbeda terhadap Kualitas Semen Segar Domba Ekor Tipis (Ovis aries) - Sirat, Muhammad Mirandy Pratama; Setio, Slamet; Alfariziki, Aksal; Siswanto; Suharyati, Sri; Dakhlan, Akhmad (AgriMalS, 2025)
This study aims to evaluate the effect of different ages on Thin-tailed Sheep (Ovis aries) on the quality of fresh semen macroscopically and microscopically. The study was conducted in July 2023 at the Teaching Farm, Animal Husbandry Department, Faculty of Agriculture, University of Lampung in the form of a case study with two age groups, namely 8-12 months (P1) and 13-18 months (P2) as many as 5 animals per age group. Observation variables are 1) macroscopic quality of semen (color, odor, pH, consistency, and volume of semen); 2) microscopic quality of semen (mass movement and motility of individual spermatozoa). Semen collection uses a special artificial vagina for Kruuser sheep. Assessment of color, odor, consistency of semen, and mass movement of spermatozoa through observation and quantification by scoring; pH using paper indicator strips; semen volume by looking at the numbers on the scale tube; mass movement and motility of individual spermatozoa through subjective assessment under a Leica DM750 binocular light microscope. Data for each variable between age groups are presented in the table of averages ± SD. Data analysis was performed statistically by comparing the two age treatment groups with the Independent Sample T-test statistical model at a 95% confidence level using SPSS series 24.0. The results showed no significant difference (P>0.05) between different age groups. The conclusion of the study is that Thin-tailed Sheep (Ovis aries) at the Teaching Farm of the Animal Husbandry Department, Faculty of Agriculture, University of Lampung at the age range of 8-18 months produce the same fresh semen quality macroscopically and microscopically, with a tendency to produce higher fresh semen quality in the 13-18 month age group.